Students’ Preferences on the Lecturers’ Written Corrective Feedback (WCF) on Their Writing Tasks: A Study at the English Language Education Study Program (ELESP), Faculty of Education, Universitas Jambi - Adrefiza Adrefiza; Habizar Habizar (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
This study analyzes students’ preferences on the lecturer’s written corrective feedback (WCF) on their writing tasks. It looks at how the students want WCF to be written, delivered, and focused on to fulfill the students’ expectations. It also analyzes the students’ preferences on the use of English or Bahasa Indonesia in the WCF to accommodate their learning needs and styles. Through an internet survey delivered to 100 students’ emails, using 5 levels of Likert scales on preferences range, the results show that the students’ preferences varied in terms of types, focuses, and ways the WCF are provided and delivered. It is an evident that many students want the lecturers to provide the correct forms of the errors, to mark and to underline the errors with corrections, and to provide explanations for every single error in their writing tasks. A significant number of the students have a low preference for the use of indirect feedback through cues and prompts. Another interesting result is the fact that many students prefer WCF to be written in Bahasa Indonesia rather than in English. It is recommended that the lecturers flexibly provide WCF according to students’ preferences and expectations to increase their writing skills.